Phytochemical Composition of Essential Oils from Cinnamomum camphora Leaves of Different Areas and their Analgesic Properties: Phytochemical Composition of Essential Oils from Cinnamomum camphora Leaves of Different Areas and … - Yang, Jinqiang; Yang, Nianyun; Fan, Luyi (Iranian Journal of Pharmaceutical Sciences, 2019)
This article was aimed to analyze the essential oils from Cinnamomum camphora leaves of four areas by GC-MS and to study their analgesic properties. Analgesia test was performed employing mouse acetic acid writhing method, hot plate method and reserpine induced migraine model, and plasma and brain tissue NO and prostaglandin E2 (PGE2) contents were determined. The major compounds from essential oils of Suzhou C. camphora leaves (SZ), Nanjing C. camphora leaves (NJ), Nantong C. camphora leaves (NT) and Lianyungang C. camphora leaves (LY) are different, but they all consist of nerolidol and (E)-α-atlantone. (E)-α-atlantone exists as the main constituent and it is first reported in this plant. In the hot plate test, NJ or LY (1 ml×kg-1 each) significantly prolonged the reaction time after 30 min treatment and plasma and brain tissue NO and PGE2 in the mice with NJ or LY (1 ml·kg-1) administration were significantly decreased. In the acetic acid-induced writhing test, NJ (1 ml×kg-1 each) significantly decreased the number of acetic acid-induced writhes in mice compared to the animals that received vehicle only. In the migraine test, Plasma NO in the mice with NJ or NT (1 ml×kg-1) and NJ (0.25 ml×kg-1) administration were significantly decreased. NJ and LY have obvious analgesic effect and the mechanism is related to the reduction of central and peripheral NO and PGE2 levels. NJ was effective on migraine mice induced by reserpine and the mechanism may be related to the inductionof NO release. NJ and LY have significantly analgesic effects in three experimental models of pain.